Analysis Of Employee Performance In The Bureau Of Government And Regional Autonomy Of The Regional Secretariat Of The Riau Islands Province - Ferdilianto, Ferdilianto; Gunawan Suharto, Didik; Bahrum, Syamsul (Indonesian Journal of Social Science Research, 2025)
This research focuses on the performance of employees at the Bureau of Government and Regional Autonomy of Riau Islands Province who are still not optimal at work. The phenomenon found is related to infrastructure facilities that are less supportive for employee work activities to work discipline that needs to be improved in the system. The theory used in this research is to use 4 main indicators, such as effectiveness and efficiency, authority and responsibility, discipline and initiative. This research uses a descriptive qualitative research method with a case study approach, so that the data obtained is in accordance with the results of the field under study. The results show that the effectiveness in completing tasks and principal runs optimally and the efficiency in the budget used is in accordance with the budget absorption obtained, in the authority and responsibility section with the issue in the spotlight is the facilities and infrastructure, on the other hand in the aspect of work discipline there is still a lack of discipline in entering the office, and the initiative is still focused as a leader rather than being a leader. The conclusion found by researchers is that authority and responsibility, discipline, and initiative are the main points that need to be improved immediately to improve quality performance.